2019
DOI: 10.1101/701730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seed-dispersal networks in tropical forest fragments: area effects, remnant species, and interaction diversity

Abstract: Seed dispersal interactions involve key ecological processes in tropical forests that help to maintain ecosystem functioning. Yet this functionality may be threatened by increasing habitat loss, defaunation and fragmentation. However, generalist species, and their interactions, can benefit from the habitat change caused by human disturbance while more specialized interactions mostly disappear. Therefore changes in the structure of the local, within fragment, networks can be expected. Here we investigated how t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Increased patch isolation, edge effects, and habitat degradation resulting from fragmentation, for instance, can negatively affects mutualisms (Magrach et al, 2014). Emer et al (2020) demonstrated in seed dispersal networks that the number of beneficial interactions decreased with increasing fragmentation. Because species interactions often affect organisms' survival and reproduction and underlie ecosystem functions, developing a predictive framework for how habitat fragmentation affects species interactions is vital for preserving biological communities within remaining habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Increased patch isolation, edge effects, and habitat degradation resulting from fragmentation, for instance, can negatively affects mutualisms (Magrach et al, 2014). Emer et al (2020) demonstrated in seed dispersal networks that the number of beneficial interactions decreased with increasing fragmentation. Because species interactions often affect organisms' survival and reproduction and underlie ecosystem functions, developing a predictive framework for how habitat fragmentation affects species interactions is vital for preserving biological communities within remaining habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study of the spatial scaling of network structure has progressed theoretically (Brose et al 2004, Pillai et al 2011, Galiana et al 2018), empirical approaches are largely missing (but see Wood et al 2015, Dáttilo et al 2019, Emer et al 2019). One exception is the work by Wood et al (2015) on the effects of sampling and spatial scale on intertidal marine food webs in Alaska.…”
Section: Introductionmentioning
confidence: 99%
“…Data available from the Dryad Digital Repository: https://doi.org/10.5061/dryad.gmsbcc2hv (Emer et al ).…”
Section: Data Availability Statementmentioning
confidence: 99%